2020
DOI: 10.1080/21679169.2020.1746830
|View full text |Cite
|
Sign up to set email alerts
|

How do the attitudes, confidence, knowledge and understanding differ in pre-registration healthcare students towards treating people with chronic pain: an observational, cross-sectional study

Abstract: Background Attitudes, knowledge and understanding may predispose practitioner adherence to clinical guidelines for chronic pain. To date there is no data exploring this in adult, mental health and paediatric nursing, or occupational therapy, podiatry and physiotherapy student healthcare professionals at the same institution. MethodsWe approached 1383 students enrolled on pre-registration healthcare programmes at a Scottish University, using the Healthcare Practitioners Pain and Impairment Relationship Scale (H… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
11
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 13 publications
(12 citation statements)
references
References 30 publications
1
11
0
Order By: Relevance
“…Whilst Carroll et al, (2020) [40] found greater improvement amongst their nursing cohorts' attitudes (1.6%-7% amongst different nursing specialities) than in this study, 2.4%, our findings accord with Amponsah et al (2020) [62] and Leahy et al (2019) [63] that final year nurses have considerable deficits in pain knowledge and attitudes. Mukoka, Olivier and Ravat (2019) [64] found more positive attitudes in their nursing and occupational therapy students but not as positive among their physiotherapy students.…”
Section: Discussionsupporting
confidence: 74%
See 1 more Smart Citation
“…Whilst Carroll et al, (2020) [40] found greater improvement amongst their nursing cohorts' attitudes (1.6%-7% amongst different nursing specialities) than in this study, 2.4%, our findings accord with Amponsah et al (2020) [62] and Leahy et al (2019) [63] that final year nurses have considerable deficits in pain knowledge and attitudes. Mukoka, Olivier and Ravat (2019) [64] found more positive attitudes in their nursing and occupational therapy students but not as positive among their physiotherapy students.…”
Section: Discussionsupporting
confidence: 74%
“…The first step towards addressing the deficiency in pain education among HCPs would be to assess current pain understanding amongst HCP students. A number of studies have explored this issue, however, these studies are generally limited to single institutions, discrete regions or only a small number of health care disciplines, reducing the generalisability of the findings [36][37][38][39][40]. If some disciplines were found to have poorer pain-related understanding than others, this difference could be explored, and pain education resources could be targeted accordingly.…”
Section: Open Accessmentioning
confidence: 99%
“…This allows new information to be processed as it can be difficult to execute in practice immediately after teaching, and confidence to practise new information takes time to develop. 8,25,60,74 Clinical records still present a potential issue of responses in keeping with social desirability although this may have less of an impact when records are observed for an extended period.…”
Section: Discussionmentioning
confidence: 99%
“…One possible factor could be the level of pain neurophysiology knowledge. 9 , 10 , 11 ) Colleary et al 9 ) conducted a two-arm randomized controlled trial among physical therapy students. The experimental group attended a 70-minute group lecture on pain neurophysiology education (PNE), which aimed to reconceptualize patient understanding of pain from a biomedical to a biopsychosocial perspective, 12 ) whereas the control group attended a 70-minute group lecture on red-flag signs and symptoms of LBP.…”
Section: Introductionmentioning
confidence: 99%